A Randomized Trial of Electrographic Flow-Guided Redo Ablation for Nonparoxysmal Atrial Fibrillation (FLOW-AF) - Reddy, Vivek Y; Langbein, Anke; Petru, Jan; Szili-Torok, Tamas; Funasako, Moritoshi; Dinshaw, Leon; Wijchers, Sip; Rillig, Andreas; Spitzer, Stefan G; Bhagwandien, Rohit; Metzner, Andreas; Kong, Melissa H; et al. (JACC. Clinical electrophysiology, 2024)
BACKGROUND: Electrographic flow (EGF) mapping enables full spatiotemporal reconstruction of organized wavefront propagation to identify extrapulmonary vein sources of atrial fibrillation (AF). OBJECTIVES: FLOW-AF (A Randomized Controlled Study to Evaluate the Reliability of the Ablacon Electrographic FLOW [EGF] Algorithm Technology [Ablamap Software] to Identify AF Sources and Guide Ablation Therapy in Patients With Persistent Atrial Fibrillation) was multicenter, randomized controlled study of EGF mapping to: 1) stratify a nonparoxysmal AF population undergoing redo ablation; 2) guide ablation of these extrapulmonary vein AF sources; and 3) improve AF recurrence outcomes. METHODS: FLOW-AF enrolled persistent atrial fibrillation (PerAF)/long-standing PerAF patients undergoing redo ablation at 4 centers. One-minute EGF maps were recorded from standardized biatrial basket positions. Patients with source activity ≥26.5% were randomized 1:1 to PVI + EGF-guided ablation vs PVI only; patients without sources ≥26.5% threshold were not randomized. Follow-up and electrocardiographic monitoring occurred at 3, 6, and 12 months. RESULTS: We enrolled 85 patients (age 65.6 ± 9.3 years, 37% female, 24% long-standing PerAF). Thirty-four (40%) patients had no sources greater than threshold; at least 1 source greater than threshold was present in 46 (60%) (EGF-guided ablation, n = 22; control group, n = 26). Patients with sources were older (68.2 vs 62.6 years; P = 0.005) with higher CHA2DS2-VASc scores (2.8 vs 1.9; P = 0.001). The freedom from safety events was 97.2%, and 95% of EGF-identified sources were successfully ablated. In randomized patients, AF-free survival at 12 months was 68% for EGF-guided ablation vs 17% for the control group (P = 0.042); freedom from AF/atrial tachycardia/atrial flutter at 12 months was 51% vs 14% (P = 0.103), respectively. CONCLUSIONS: In nonparoxysmal AF patients undergoing redo ablation, EGF mapping identified AF sources in 60% of patients, and could be successfully ablated in 95%. Compared with PVI alone, PVI + source ablation improved AF-free survival by 51% on an absolute basis. (FLOW-AF: A Study to Evaluate the Ablacon Electrographic FLOW EGF Technology [A Randomized Controlled Study to Evaluate the Reliability of the Ablacon Electrographic FLOW (EGF) Algorithm Technology (Ablamap Software) to Identify AF Sources and Guide Ablation Therapy in Patients With Persistent Atrial Fibrillation]; NCT04473963).
Keywords: Female; Electrophysiologic Techniques, Cardiac; Atrial Fibrillation; elektrofyziologické techniky kardiologické; výsledek terapie; ženské pohlaví; Catheter Ablation; basket catheter; lidé; katetrizační ablace; Treatment Outcome; Algorithms; Electrocardiography; elektrokardiografie; panoramic mapping; Reoperation; reoperace; persistent atrial fibrillation; Male; Aged; electrographic flow mapping; algoritmy; fibrilace síní; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans